Tyler Wilson: capstone - Wilson, Tyler, artist (Colorado State University. Libraries, 2021)
The artist's statement: I create paintings and prints with busy compositions that employ definitive strokes and line, emotive color, and thoroughly layered textures. Using these physical techniques, my large-scale, mixed media artworks portray the fatigue of everyday rapidity, the struggle of existence, and the interactivity between individuals. To do this, my paintings employ ordinary materials of everyday use that promote decay, variability, and the "human" in the craftsmanship of my work. I've always been attracted to the cracks in the paint rather than the painting. I would go into museums and look at the way the paint would decay on old oil paintings. I would bring this lens of the imperfect out into the streets and notice all the dirt on the ground, the lichen growing on the walls, and the slight differences of texture in the concrete. My main themes revolve around the ordinary person, perfect imperfections, and the blessings of mediocrity. I connect dirtiness, normality and the typical person together to create a less perfect art that doesn't pander to the mediocre, but attempts to mimic it. From my perspective, the less perfect a piece is; the more interesting it becomes. The flaws and imperfections of an object is what makes that object what it is, and to idealize an object is to make what it is not. The idea of imperfection is presented in two ways: 1) the treatment of the materials (physicality), and 2) the narrative of the piece (informativeness). Both elements are key to having an interesting artwork because they lean on each other and cater to different viewers, which increases the piece's accessibility and viewer retention. The texture draws the viewer in close while the narrative makes them take a step back. My colour palette sways towards red and warm colours because they are more violent and expressive. The technique of my mark making is loose with a brush and harsh with a palette knife. Recently, I've picked up the practice of a cycle of addition-removal-addition which allows me to be subtractive with painting and create dirtier-looking images. In addition, most of my works are large because I want the viewer to be absorbed into the piece rather than feel like they are looking through a window. My work would almost shrink if placed into a frame which is why I prefer to keep them unframed. My practice is inspired by countless art historical figures such as Jean-Michel Basquiat, Robert Rauschenberg, Jean Dubuffet, Barnett Newman, Sigmar Polke, Anselm Kiefer, and many more that I cannot list for the sake of brevity. I think perhaps the biggest inspiration is Jean Dubuffet and his idea of the art brut, and since I am already too corrupted in the art historical world, I can only emulate Jean Dubuffet's vision and attempt to marry art culturel and art brut. I put a contemporary spin of this and address hopelessness, loss of identity, and the creation and destruction of meaning in ordinary people while creating art that attempts to convince ugliness and naivety to look beautiful. This is in direct conflict with contemporary push towards the corporate and the clean with brands controlling more and more of the public attention.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking